2022
DOI: 10.1002/jimd.12551
|View full text |Cite
|
Sign up to set email alerts
|

EXPLORE B: A prospective, long‐term natural history study of patients with acute hepatic porphyria with chronic symptoms

Abstract: One-year data from EXPLORE Part A showed high disease burden and impaired quality of life (QOL) in patients with acute hepatic porphyria (AHP) with recurrent attacks. We report baseline data of patients who enrolled in EXPLORE Part B for up to an additional 3 years of follow-up. EXPLORE B is a long-term, prospective study evaluating disease activity, pain intensity, and QOL in patients with AHP with ≥1 attack in the 12 months before enrollment or receiving hemin or gonadotropin-releasing hormone prophylaxis. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Currently, a significant and unresolved debate exists in the literature regarding the natural progression of patients with Acute Hepatic Porphyria. There is ongoing uncertainty surrounding the origin and mechanisms underlying the chronic symptoms observed in patients, leading to a dichotomy in the classification of patients into “sporadic attacks” and “recurrent attacks.” This classification dilemma has contributed to several uncertainties regarding the optimal medical management and treatment strategies for these individuals ( 6 , 8 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a significant and unresolved debate exists in the literature regarding the natural progression of patients with Acute Hepatic Porphyria. There is ongoing uncertainty surrounding the origin and mechanisms underlying the chronic symptoms observed in patients, leading to a dichotomy in the classification of patients into “sporadic attacks” and “recurrent attacks.” This classification dilemma has contributed to several uncertainties regarding the optimal medical management and treatment strategies for these individuals ( 6 , 8 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…• Intense pain, mainly in the abdomen, requiring hospital admission attacks. 33 In a different observational study, chronic symptoms were reported in 85% of AIP patients with sporadic attacks (< four attacks/year) and 46% of patients with latent AIP (no attacks). 34 Chronic pain is usually the most commonly reported symptom, followed by tiredness, anxiety, nausea and sleeping disorders.…”
Section: Laboratory Findingsmentioning
confidence: 96%